Wireless powered wearable micro light-emitting diodes. (January 2019) - Lee, Han Eol; Lee, Daewon; Lee, Tae-Ik; Shin, Jung Ho; Choi, Gwang-Mun; Kim, Cheolgyu; Lee, Seung Hyung; Lee, Jae Hee; Kim, Yong Ho; Kang, Seung-Mo; Park, Sang Hyun; Kang, Il-Suk; et al.
Abstract: Wearable displays are considered as a bilateral communication tool in the hyperconnected era. Although several electronic clothing display was demonstrated, high power consumption issue still remained. Here, we present wireless powered wearable μLEDs (WμLEDs) with excellent stability. A custom-designed wireless power supply system operated a 30 × 30 WμLED array on a fabric. The WμLED stability was intensively investigated under bending, stretching, 85 °C/85% relative humidity and artificial sunlight conditions, showing the suitability of WμLED outdoor usage. Finally, a passive-matrix WμLED display successfully emitted a brilliant red glow on a fabric. Graphical abstract: fx1 Highlights: Wireless powered wearable μLEDs (WμLEDs) with excellent stability was realized by a custom-designed wireless energy supply system on a fabric. WμLED stability was investigated under bending, stretching, 85 °C/85% relative humidity and artificial sunlight conditions, showing the suitability of WμLED outdoor usage. A passive-matrix WμLED display successfully emitted a brilliant red glow on a fabric.